Monte Carlo simulations for XIDer, a novel digital integration X-ray detector for the next generation of synchrotron radiation sources. (1st January 2022) - Collonge, M.; Busca, P.; Fajardo, P.; Williams, M.
Abstract: This work presents the first simulation results of the incremental digital integration readout, a charge-integrating front-end scheme with in-pixel digitisation and accumulation. This novel readout concept is at the core of the XIDer (X-ray Integrating Detector) project, which aims to design 2D pixelated X-ray detectors optimised for high energy scattering and diffraction applications for the next generation of synchrotron radiation sources such as the ESRF Extremely Brilliant Source (EBS). The digital integration readout and the XIDer detector open the possibilities for high-duty-cycle operation under very high photon flux, fast frame-rate and high dynamic range with single-photon sensitivity in the 30–100 keV energy range. The readout method allows for noise-free effective X-ray detection. The digital integration concept is currently under investigation to evaluate the impact of main critical design parameters to identify the strengths and weaknesses of the readout scheme and consequently to propose refinements in the final implementation. Simulations have been performed with a dedicated Monte Carlo simulation tool, X-DECIMO, a modular Python package designed to recreate the complete detection chain of X-ray detectors for synchrotron radiation experiments. Losses and non-linearities of the readout scheme are simulated and quantified. In addition to presenting simulation results for this novel readout scheme, this work underlines the potential of the approach and some of its limitations.